Reflection of the pattern of cortical activation in the phase structure of the human EEG - Getmanenko, O. V.; Belov, D. R.; Kanunikov, I. E.; Smit, N. Yu; Sibarov, D. A. (Neuroscience and behavioral physiology, 2007)
A total of 22 healthy subjects in the EEG laboratory and 62 patients in the clinical functional diagnostic unit were studied. Spontaneous EEG recordings were made using the 10-20 scheme relative to combined ear electrodes in the state of rest with the eyes closed and open and during various functional loads. Traces were analyzed by computer animation of the EEG phase structure. The main concept of the method for extracting phase structure was based on not using a single reference lead. Time shifts were measured only between neighboring electrodes, with the result that the oscillations being compared were highly coherent. Time discordance was assessed in terms of the shift in the peak of the cross-correlation function. The results showed that from the point of view of phase structure, the differences between the high-and low-frequency EEG rhythms were purely quantitative. Qualitatively, the properties of the rhythms were identical and were reduced to slow (in the seconds range) oscillations of phase shifts. Low-frequency activity was characterized by large (in absolute terms, msec) phase shifts from electrode to electrode as compared with high-frequency activity. The phase shifts of potentials formed a structure which was overall very similar in different subjects and was reproduced in different leads. The initial appearance of EEG waves was statistically linked with the main sensory projections--the visual (occipital areas), auditory (temporal areas), and somatic (parietal areas), with addition of the frontal areas. Rearrangement of phase leadership in favor of the occipital pole at the expense of both temporal areas was observed on opening the eyes. This appears to depend on the level of sensory influx to this cortical area from the thalamus. It is suggested that the direction of the phase gradient reflects a gradient of cortical current density parallel to the surface. This can be used to locate compact sources lying close to the surface.